The calcium gluconate filled epoxy waterborne primer coating for marine application / Nurul Hanis A. Lamlee ... [et.al.] - A. Lamlee, Nurul Hanis; Mohamed, Nur Raihan; Ahmad, Zuliahani; Abu Hasan Shaari, Helyati; Baharudin, Adzrie; Musa, Luqman; Abd Aziz, Azniwati; Din, Siti Nor (Research Management Institute (RMI), 2024)
The synthesis of corrosion protection in the waterborne epoxy primer coating, which included calcium gluconate (CG), was synthesized. Various compositions of CG, ranging from 0 to 8 grams were applied to the carbon steel substrate using this water-based epoxy coating. The investigations included FTIR characterization, Tafel plot polarization, immersion, adhesion, and hardness tests. The presence of CG at 2868.88 cm-1, corresponding to calcium ion (Ca2+), was confirmed by the FTIR result, while the epoxy functional group was detected at 1506 cm-1. Furthermore, it was observed that the immersion test, hardness test, and adhesion test revealed that the highest formulation for corrosion inhibition was 8 g of CG, which also exhibited a lower corrosion rate of 0.262 mmpy, improved mechanical properties (4H), and 0 % area removed. The presence of CG, which facilitated interaction with the epoxy resin through coordination between gluconate ions and Ca2+ ions, was believed to be responsible for increasing the concentration of dissolved Ca2+ ions in the solution. This, in turn, enhanced the formation of Ca(OH)2 on the surface of the aluminium alloy, leading to corrosion inhibition. Ultimately, the utilization of CG as an anti-corrosive pigment resulted in a reduction of corrosive properties and an enhancement of mechanical properties in waterborne primer coatings.